Impact of Eye Drops Instillation of Antihypertensive Drugs on the Refractive Power of the Cornea - D. F. Belov; V. P. Nikolaenko (Oftalʹmologiâ, 2020)
Purpose: to assess effect of eye drops instillation on the refractive power of the cornea and potential intraocular lens (IOL) power calculation errors appearing related within.Patients and methods. There were 478 patients divided in 3 groups: 1st — patients without glaucoma and topical treatment (n = 325); 2nd — individuals with primary open angle glaucoma (POAG) on treatment (n = 122); 3rd — patients with POAG and previous trabeculectomy (TE) without using eye drops (n = 31). For each patient keratometry was performed by IOL-Master 500. Mean preoperative keratometry and corneal astigmatism were compared within IOL calculation error received by Barrett Universal II formula 1 month after phacoemulsification (PE).Results. Mean keratometry was significantly (p < 0.001) less (0.6 D) at the 1st group (44.00 ± 1.96 D) versus 2nd group (44.6 ± 1.76 D). Cancellation of topical eye drops due to TE leads to insignificant decline of corneal curvature (from 44.6 ± 1.76 D to 44.1 ± 1.59 D). There was no any difference in corneal astigmatism level between study groups (0.92 ± 2.23 D, 0.8 ± 0.59 D and 0.86 ± 0.50 D for groups respectively) as like as no distinction in IOL calculation error in these groups (–0.08 ± 0.57 D, –0.06 ± 0.6 D and 0.003 ± 0.61 D). However, men have more flatter cornea (43.6 ± 1.98 D) than women (44.4 ± 1.80 D) (p < 0.001). Mean keratometry at the age group 60–74 years was less (43.7 ± 2.3 D) than at 75–90 years (44.4 ± 1.54) (p = 0.002).Conclusion. Patients with coexistent cataract and glaucoma on treatment require special attention in IOL calculation. To avoid keratometric errors it is recommended to prescribe lubricants and change hypotensive eye drops to preservative-free analogs to form a stable tear film.